The brainstem connectome database - Oliver Schmitt (Scientific Data, 2022)
Measurement(s) brainstem Technology Type(s) tract tracing metastudy Factor Type(s) brain region Sample Characteristic - Organism Rattus rattus Sample Characteristic - Environment Experimental setup Sample Characteristic - Location Germany